Supplementation strategies to control propionic acid accumulation resulting from ammonia inhibition in dry anaerobic digestion: osmoprotectants, activated carbon and trace elements - Rocamora, Ildefonso; Wagland, Stuart T.; Hassard, Francis; Villa, Raffaella; Peces, Miriam; Fotidis, Ioannis A.; Simpson, Edmon W.; Fernández, Oliver; Bajón Fernández, Yadira (Elsevier, 2025)
Propionic acid accumulation in anaerobic digestion is a common sign of inhibition at high ammonia levels. To mitigate accumulation three supplementations were tested: osmoprotectants, trace elements and activated carbon. Activated carbon and osmoprotectants (MgCl2) achieved a 28 % increase in methane yield and a 3-fold reduction in hydrogen partial pressure compared with the control. Trace elements supplementation increased methane formation by 18 % without preventing instability. No supplementation avoided propionic accumulation, although MgCl2 delayed it. Activated carbon and MgCl2 supported proliferation of strict hydrogenotrophs, increasing microbial redundance with expected positive impacts on process resilience. Evidence beyond previous studies on the role of retention time as a control parameter of versatile archaea's methanogenic pathway is also provided. As retention time is reduced, syntrophic acetate oxidising bacteria are washed out of the system, likely resulting from an increase in their doubling time with inhibitors accumulation, preventing hydrogenotrophic methanogenesis and supporting previous observations of Methanosarcina being forced to conduct acetoclastic methanogenesis. Longer retention times to accommodate longer doubling times or alleviation of inhibition with activated carbon and MgCl2 supported retention of syntrophic acetate oxidising bacteria, enabling strict hydrogenotrophic archaea to proliferate. These supplementations would allow operation of industrial scale ADs at shorter retention times and higher throughputs. Results suggest that osmoprotectants and activated carbon addition were linked to a reduction in archaea's osmotic pressure and enhanced direct interspecies transfer, respectively, leading to increased methane formation despite propionic levels.
Keywords: Propionic degradation index; Trace elements; Inhibited steady state; Organic fraction municipal solid waste; Activated carbon; 40 Engineering; 4011 Environmental Engineering; 3406 Physical chemistry; 4004 Chemical engineering